Clinical Utility of Two- and Three-Dimensional Visuoconstructional Tasks in Mild Cognitive Impairment and Early Alzheimer's Disease. (4th October 2019) - Martins-Rodrigues, Rafaela; da Fonsêca, Égina Karoline Gonçalves; Lucena-Alves, Silvia Sanaly; Contador, Israel; Trojano, Luigi; Grossi, Dario; Fernández-Calvo, Bernardino
Abstract: Objective: The aim of this study was to investigate whether different types of visuoconstructional abilities are useful to distinguish individuals with mild cognitive impairment (MCI) and Alzheimer's disease (AD) from healthy controls (HCs). Method: We selected 20 patients with MCI and 14 with AD diagnosis based on standard criteria. The neuropsychological performance of MCI and AD groups were compared with that of a group of 11 HCs using a standard neuropsychological battery and visuoconstructional tasks that differed difficulty and type of implicated skills (graphomotor vs. non-graphomotor): two-dimensional (Clock Drawing Test, CDT; Block Design, BD; and Visual Puzzles, VP) and three-dimensional Block Construction (TBC). Results: AD group scored significantly lower than HCs in BD, VP and TBC tasks, but no significant differences were found between HCs and MCI. CDT (copy condition) scores did not differ significantly among the groups. The receiver operating characteristic analysis showed that BD [sensitivity (se) = .85, specificity (sp) = .90, Youden index (J) = .76], VP (se = .78 and sp = .72, J = .51) and TBC (se = .71, sp = 100, J = .71) were accurate tasks to discriminate between AD and HCs. Moreover, BD tasks (se = .85, sp = .70, J = .55) and TBC (se = .71, sp = .80, J = .51) showed fair accuracy to differentiate between MCI and AD groups. Conclusions: These findings indicate that non-graphomotor visuoconstructional tasks are already impaired in the early stages of AD, but are preserved in MCI individuals when compared with HCs.